On the Torsion of Asymmetric Bearing Systems of Multi-Storey Buildings - V. A. Lyublinskiy (Железобетонные конструкции)
Asymmetric arrangement in the plane of vertical bearing elements, ladders, stiffness elements is to the occurrence of eccentricity between center of rigidity and center of mass. Later, under the action of a horizontal load, torsion occurs in asymmetric load-bearing systems. This paper considers the resistance of multi-storey buildings during torsion caused by an asymmetric arrangement of vertical load-bearing objects.The object of the study was the carrier system of a residential monolithic multi storey building with an implicitly non-coinciding center of rigidity and center of mass. Numerical simulation for a horizontal load determined the stress-strain state of vertical reinforced concrete structures. The change in forces and displacements in the pylons during the torsion of a multi-storey building is obtained. The results of the analysis carried out can be used in the design of compressed and bending reinforced concrete structures subject to torsion.